Al-Ghazalis Views on the Heart, the Spirit and the Soul: A Comparison Between Ihya’ ’Ulum Al-Din and Al-Risalah Al-Laduniyyah - Saari, Che Zarrina (Jurnal Usuluddin, 1998)
Imam al-Ghazali expresses many ideas on heart (al-Qalb), spirit (al-Ruh) and soul (al-Nafs), in his different works. This article tries to compare his views on these subjects between the doctrine contains in Ihya’ ’Ulum al-Din and al-Risalah al-Laduniyyah.